2012
DOI: 10.1152/jn.00374.2011
|View full text |Cite
|
Sign up to set email alerts
|

β2-Adrenergic receptor supports prolonged theta tetanus-induced LTP

Abstract: The widespread noradrenergic innervation in the brain promotes arousal and learning by molecular mechanisms that remain largely undefined. Recent work shows that the β(2)-adrenergic receptor (β(2)AR) is linked to the AMPA-type glutamate receptor subunit GluA1 via stargazin and PSD-95 (Joiner ML, Lise MF, Yuen EY, Kam AY, Zhang M, Hall DD, Malik ZA, Qian H, Chen Y, Ulrich JD, Burette AC, Weinberg RJ, Law PY, El-Husseini A, Yan Z, Hell JW. EMBO J 29: 482-495, 2010). We now demonstrate that the β(2)AR plays a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
116
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(125 citation statements)
references
References 51 publications
8
116
1
Order By: Relevance
“…We have shown that the effects of ISO are mediated through b1-but not b2-adrenergic receptors, as the facilitative effects of ISO + CCh were blocked by CGP (b1 antagonist) but were preserved in the presence of ICI (b2 antagonist). Recent data suggest that prolonged u-frequency stimulation paired with ISO application induces LTP requiring b2-ARs but not b1 (Qian et al 2012). However, prior evidence generated using b1-AR KO mice found deficits in Q + ISO LTP that was not observed in b2 KOs (Winder et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that the effects of ISO are mediated through b1-but not b2-adrenergic receptors, as the facilitative effects of ISO + CCh were blocked by CGP (b1 antagonist) but were preserved in the presence of ICI (b2 antagonist). Recent data suggest that prolonged u-frequency stimulation paired with ISO application induces LTP requiring b2-ARs but not b1 (Qian et al 2012). However, prior evidence generated using b1-AR KO mice found deficits in Q + ISO LTP that was not observed in b2 KOs (Winder et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively low concentrations of ISO or the presence of a second neuromodulatory agonist may also explain the favored initiation of signal mechanisms downstream of b1-ARs, whereas the Qian et al (2012) data were based on the presence of ISO alone which may necessitate the engagement of both receptor subtypes. Future research combining receptor subtype-specific agonists will be required to further delineate the putative interactions of these neuromodulatory signaling mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…For example, b-AR activation enables the induction of protein synthesis-dependent L-LTP by a single 100-Hz train of HFS (Gelinas and Nguyen 2005;Ma et al 2011). Moreover, u-pulse stimulation (TPS; 150-900 stimulation pulses delivered at 5 -10 Hz), a pattern of synaptic stimulation that alone has little or no lasting effect on synaptic strength, can induce LTP if delivered in the presence of b-AR agonists (Thomas et al 1996;Katsuki et al 1997;Moody et al 1998;Winder et al 1999;Brown et al 2000;Gelinas and Nguyen 2005;Havekes et al 2012;Qian et al 2012). The induction of LTP by spike-timing-dependent plasticity protocols, where excitatory postsynaptic potentials elicited by presynaptic fiber stimulation are paired with postsynaptic action potentials evoked by current injection through an intracellular recording electrode, is also enhanced by b-AR activation (Lin et al 2003;Seol et al 2007;Makino et al 2011).…”
Section: B-adrenergic Receptors Facilitate Long-lasting Hippocampal Smentioning
confidence: 99%
“…For example, Qian et al (2012) reported that b2-AR activation supports prolonged hippocampal u-tetanus-LTP (Qian et al 2012), which is an important form of synaptic plasticity for hippocampal functions. McGaugh and co-workers (1991) reported that the infusion of the b2-AR agonist clenbuterol into the amygdala immediately after training enhances memory retention in an inhibitory avoidance task (Introini-Collison et al 1991).…”
mentioning
confidence: 99%